Cambridge review of international affairs (Carfax Publishers, Taylor & Francis Group, 2009)
The Cambridge Review of International Affairs is a peer-reviewed journal promoting debate on international affairs across the social sciences - including international studies, international relations, international law, and international political economy - and between scholars and policymakers.